Values of National Character Education Perspective alQur'an Surah Luqman Verses 12-19 to Support the Golden Generation - Latifah Salsabil Nikmah; Muthoifin Muthoifin (Prosiding University Research Colloquium, 2022)
The purpose of this study is to analyze whether the 18 values in national character education that have been set by the Indonesian Ministry of National Education are following the Qur'anic perspective of character education in Surah Luqman verses 12-19. The data collection method used is literature study, namely by collecting and analyzing documents sourced from primary data from Luqman's letter, and secondary sources from journals, books, proceedings, and various other easily accessible scientific articles. This study uses a qualitative type, with a content analysis approach, and theological normative. The results of the study show that 18 values of national character that have been set by the Indonesian Ministry of National Education are following the wise values contained in the perspective of character education in the Qur'an, Surah Luqman verses 12–19, both explicitly and implicitly, dhohiriyah and substance, so that the eighteen national characters can be implemented for the development of Indonesia's golden generation.